A study on scheduled waste at the laboratory Of UTHM Pagoh campus - A. Hamid, Hazren; Harun, Hasnida; Mohamed Sunar, Norshuhaila; Ahmad, Faridahanim (Penerbit UTHM, 2020)
Scheduled Waste Management has different significance and classification according to the country. For example, most of the waste is categorized under hazardous waste (HW) because of their physical characteristics that appropriate with HW. HW can be categorized on the basis of their hazardous nature which includes toxicity, flammability, explosively, corrosively and biological infectivity [1]. In Malaysia, hazardous waste is well-defined as any waste falling within the categories of waste listed in the First Schedule of the Environment Quality (Scheduled Wastes) Regulation 2005.